Development of a Contextual-Based Learning Module for Quadrilateral Material - Niluh Sulistyani; Catarina Sarah Devi (Edumaspul: Jurnal Pendidikan, 2024)
Learning modules are one of the learning resources that can be used by teachers and students in the learning process. This research aims to develop a mathematics learning module with valid contextually based quadrilateral material. This research is Research and Development with the Thiagarajan model. Due to time constraints, researchers only carried out 3 stages out of 4 stages, namely Define, Design, and Develop. Apart from learning modules for students, this research also develops teacher guides related to these learning modules. The results of this research showed that the contextual-based rectangular material learning module was said to be valid with a percentage of 83.12% so the learning module was suitable for use by students in the learning process.